2010
DOI: 10.1080/00036810903277135
|View full text |Cite
|
Sign up to set email alerts
|

Energy thresholds for the existence of breather solutions and travelling waves on lattices

Abstract: We discuss the existence of breathers and of energy thresholds for their formation in DNLS lattices with linear and nonlinear impurities. In the case of linear impurities we present some new results concerning important differences between the attractive and repulsive impurity which is interplaying with a power nonlinearity. These differences concern the coexistence or the existence of staggered and unstaggered breather profile patterns.We also distinguish between the excitation threshold (the positive minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In this point of view, (1.1) seems to be of particular interest due to the interplay and the expected competition of the nonlinear hopping and the generalized power nonlinearities. Extending the arguments based on variational methods [24][25][26] and the fixed point approach of [27] to establish the existence of solutions (1.8), we show the existence of lower bounds on the power of breathers on either finite or infinite lattices. The bounds depend explicitly on the dimension, and the nonlinear lattice parameters, as well as on the frequency of the solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this point of view, (1.1) seems to be of particular interest due to the interplay and the expected competition of the nonlinear hopping and the generalized power nonlinearities. Extending the arguments based on variational methods [24][25][26] and the fixed point approach of [27] to establish the existence of solutions (1.8), we show the existence of lower bounds on the power of breathers on either finite or infinite lattices. The bounds depend explicitly on the dimension, and the nonlinear lattice parameters, as well as on the frequency of the solution.…”
Section: Introductionmentioning
confidence: 99%
“…It is crucial to remark that the set of parameters for which the excitation threshold R thresh is apparent suggests that the energy bounds R crit are not sharp as thresholds for existence/nonexistence. In particular, when R crit is the value derived by the fixed-point approach, it is observed that R thresh > R crit , [24,26]. For further discussions on the excitation threshold for FPU and Klein-Gordon lattices we refer the interested reader to [30].…”
Section: Introductionmentioning
confidence: 99%
“…51 ). We also remark that the results can be extended in the case of the infinite lattice Z N by implementing the concentration compactness arguments 51,53 .…”
Section: Discussionmentioning
confidence: 99%
“…If R < R thresh then I R = 0 and there is no ground state minimizer of (53). C. If R > R thresh then I R < 0 and there exists a minimizer of the variational problem (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation